Changing driver behavior during floods: Testing a novel e-health intervention using implementation imagery. (April 2021) - Hamilton, Kyra; Keech, Jacob J.; Peden, Amy E.; Hagger, Martin S.
Highlights: The study used a randomized controlled trial design. Short-term changes in intentions were observed in both groups. Short-term changes in subjective norms were observed in both groups. Changes in subjective norms appeared to persist for the intervention group. Changes greater for those who indicated an intention to drive into floodwater. Abstract: We tested the efficacy of a novel implementation imagery intervention ( N = 460) in promoting safer intentions regarding driving into floodwater post-intervention, and at a four-week follow-up using a pre-registered randomized controlled design. Results showed that the intervention reduced intentions and subjective norms regarding driving into floodwater. The control condition also improved on intentions and subjective norms, but the changes appeared to only be maintained at the follow-up for the intervention group and the between group difference at the follow-up was not significant based on our pre-specified cutoff level for statistical significance of 0.01. Results also indicated that changes in intentions may be stronger for males than females. Further exploratory analyses indicated that the intervention showed greater effects on post-intervention intentions, subjective norms, perceived behavioral control, perceived severity, anticipated regret, barrier self-efficacy, and action planning in individuals who indicated a modest level of intention to drive into floodwater prior to the intervention.